Green and clean process to obtain low degree of polymerisation xylooligosaccharides from almond shell. (20th December 2019) - Singh, Ramkrishna D.; Nadar, Cresha Gracy; Muir, Jane; Arora, Amit
Abstract: This work presents a green and chemical free sequential process consisting of autohydrolysis, enzymatic treatment, and membrane assisted refining for the valorization of almond shell into the low degree of polymerisation xylooligosaccharides. For autohydrolysis, the temperatures (180, 200, and 220 °C) with different reaction times were evaluated. Further, enzymatic treatment of the autohydrolysate was performed to increase the concentration of low degree of polymerisation xylooligosaccharides. For enzymatic treatment, three different doses (5, 10, and 15 U) was used, and the optimum dose estimated using statistical analysis. Finally, the XOS rich enzyme liquor was subjected to membrane assisted refining using 1 kDa and 250 Da membranes to obtain XOS concentrate. Under the optimal condition (200 °C, 5 min) of autohydrolysis, about 54.5% of xylan could be obtained as oligosaccharides. However, the autohydrolysate was composed of 3.5% (w/w of biomass) of low degree of polymerisation xylooligosaccharides (xylobiose and xylotriose). The enzymatic treatment using 10 U of the enzyme could increase the concentration of low degree of polymerisation xylooligosaccharides to 8.2% (w/w of biomass). Finally, the membrane-assisted refining could recover 69.1 ± 0.1% (w/w) of produced xylooligosaccharides. Graphical abstract: Image 1 Highlights: Autohydrolysis solubilize 54.5% hemicellulose from almond shell. Enzymatic hydrolysis increases concentration of low degree of polymerisation XOS. Sequential membrane separation gives concentrated XOS liquor. Final concentrate is rich is xylobiose (44.6%) and xylotriose (12.4%).